Konsep dan Implementasi Pendidikan Karakter di Universitas Muhammadiyah Prof. Dr. Hamka Jakarta - Tohirin Tohirin (Badan Litbang dan Diklat Kementerian Agama RI, 2016)
This research is aimed at acknowledging the concept and implementation of character education in the Prof. DR. HAMKA (UHAMKA) Muhammadiyah University, Jakarta. As a university under the Muhammadiyah, character education is the main objective of the education implemented in UHAMKA. This research is a qualitative research In this context, the researcher is the main instrument collecting and interpreting the existing data. Data were collected through in-depth interviews with a number of UHAMKA key informants and written documents related to character education. The research results show that UHAMKA has developed a character education model through the AIKA curriculum. This AIKA curriculum has been formulated in such a manner with systematic management from the aspects of policies, contents and organization so that it can be referred to as a model. However, the application of the AIKA curriculum has not reached the expected target. There are many things that must be reformed in order to achieve the objective of character education in UHAMKA especially those related to the relatively cognitive material contents and learning method.